ANALISIS MOTIVASI PEMBELAJARAN DALAM SURAT AL KAUTSAR MENURUT PEMIKIRAN Dr. KH. ABDUL SYAKUR YASIN, MA - Sumarta; Faiz Musthofa Abbas; Dinata Firmansyah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
The Qur'an is not only a source of legal (kauniyah) verses but also contains many pearls of wisdom that can serve as motivation in life. Many renowned motivators around the world have cited and drawn inspiration from these verses. However, most Muslims treat the Qur'an merely as an ornament or complement. One such gem is Surah Al-Kautsar, which has short verses that are easy to memorize and remember. This study aims to examine the interpretation of the verse in Surah Al-Kautsar from the perspective of Dr. KH. Abdul Syakur Yasin, MA, and its relevance in today's social context. The research focuses on understanding the deeper meanings of this verse and its application in contemporary social life. Using a linguistic analysis approach, this study will explore the meaning of the verse within the socio-cultural conditions of today's Muslim community. The primary objective is to uncover the relevance of the wisdom in Surah Al-Kautsar and its potential impact on modern life, especially in fostering a mindset of gratitude and positive thinking. Preliminary findings suggest that this interpretation could provide valuable insights into contemporary spiritual motivation.